Enablers and Inhibitors of the EU and US Response to Climate Change: How the EU Pulled Ahead - Stevens, McKenzie (Colloquium: The Political Science Journal of Boston College, 2021)
Climate change is by far one of the most significant issues facing the world today, yet still lacks the comprehensive multilateral response needed to address it. The EU has substantially increased its relevance on the global stage by assuming a leadership role in international climate mitigation efforts. Through enacting ambitious climate policy across its member states, the EU aims to spur similar action within other major greenhouse gas-emitting countries such as the US. With this in mind, to what extent has the EU been more successful than the US at addressing climate change through policy initiatives? Additionally, what are the underlying factors that have enabled this? These questions will be explored through a comparative analysis of the current emissions trajectories, climate policies, and public perceptions of climate change in both the EU and the US to determine what circumstances allow for meaningful climate action.